Learning from Green Community Practices at Morino Office, Japan: Insights from Hybrid Reflective Field Exploration: Belajar dari Praktik Komunitas Ramah Lingkungan di Morino Office, Jepang: Perspektif Eksplorasi Reflektif Berbasis Interaksi Hibrida - Devie Rahmawati; Wiratri Anindhita; La Mani; Muhammad Zaky Ramadhan (Lembaga Riset dan Inovasi Masyarakat Madani, 2026)
Environmental sustainability is a shared responsibility of environmental activists, academics, and communities in managing natural resources responsibly. This community engagement initiative aims to introduce a community-based approach through the Morino Office green community model so that environmental activists and communities can work together to safeguard environmental sustainability. This activity employed a participatory and needs-based approach and was carried out at Morino Office, located in Fujimi, Japan. The participants consisted of five Morino Office staff members, three academics, and ten environmental activists. The results show that Morino Office, as an environmentally friendly workspace, supports both economic and ecological functions within urban and rural communities. The Morino Office green community model integrates sustainable lifestyles, village revitalisation, community participation, and circular economy principles in mountainous areas. Therefore, this community-based approach can serve as a practical concept for strengthening environmental sustainability. The implication of this activity is that green community development can bridge urban and rural communities in protecting the environment through environmentally friendly workspaces.